Effective coaching: Case studies from professional rugby union and rugby leaugue teams in Australia - Bennie, A.; O'Connor, D. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Many coaches aim to emulate the tactics, training strategies and mindsets of professional coaches in order to achieve excellence in their given sport. Worldwide, the media provides intense scrutiny of professional sport yet there has been little academic research conducted within this unique context. This study investigated the concept of effective coaching based on the perceptions and strategies of professional Australian sport coaches and players from rugby league and rugby union. It also explored what professional coaches do, and what makes coaches effective in their day-to-day roles. Methods This study examined the perceptions (through interviews) and behaviours (via observations) of four, male, professional coaches and 17 athletes from Australia. The participants were from two teams; one from the National Rugby League and one from the Super 14 (now Super 15) rugby union. Interviews enabled participants to discuss their interpretations of their unique professional contexts from their own point of view while the observational data identified various coaching strategies and interactions with players during training and competition contexts. Results and Discussion A key finding in this research is that the humanistic ideals of developing the player and the person - once thought to be incompatible with principles of performance sport (see Lyle, 2002) - now form a prominent part of the professional sport landscape and effective coaching in Australia. Similarly, the trend towards empowerment and facilitative coaching suggests that the autocratic, one-size-fits-all approach has declined in the modern professional sports contexts in this study. The results also showed that it is important for coaches to employ their own unique approach to leadership, as there appears to be no single recipe for success and effectiveness in sport coaching. Here, the coach`s personal approach to coaching needs to align with the players` preferred coaching style for the coach to be considered effective. Conclusion Participants from rugby union and rugby league suggested that effective coaches placed less focus on the technical and tactical elements of coaching in comparison to the emphasis placed on the need for professional coaches to be good at working with people. Hence, professional coaches in modern sport settings require more than just sport-specific knowledge and an ability to effectively instruct or lead a team. This presentation will discuss specific examples from the current study in relation to previous literature and highlight various implications of the findings for coach education programs.